1995
DOI: 10.1111/j.1476-5381.1995.tb16389.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of semotiadil fumarate, a novel calcium antagonist, in rat experimental angina model

Abstract: 1 The aim of the present study was to determine whether antianginal efficacy of semotiadil fumarate (SD-321 1), a structurally novel calcium antagonist, is distinct from those of diltiazem, nifedipine and nisoldipine.2 First, the duration of the inhibitory effects of semotiadil was compared with that of other Ca2l antagonists in rat experimental angina evoked by vasopressin. Semotiadil (10 mg kg-', p.o.) was effective for at least 9 h in the anginal model and those effects of semotiadil were longer-lasting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Changes in ST-segment were used as an index of ischemic severity. According to the previous report (2), the fall of S-wave was regarded as the fall of ST. Maximal S-wave depression was observed 4 -5 min following AVP injection, consistent with previous reports (10,11). Both benidipine (3 and 10 m g / kg) and diltiazem (300 and 1000 mg/ kg) significantly inhibited the S-wave depression in a dose-dependent manner (Fig.…”
supporting
confidence: 80%
“…Changes in ST-segment were used as an index of ischemic severity. According to the previous report (2), the fall of S-wave was regarded as the fall of ST. Maximal S-wave depression was observed 4 -5 min following AVP injection, consistent with previous reports (10,11). Both benidipine (3 and 10 m g / kg) and diltiazem (300 and 1000 mg/ kg) significantly inhibited the S-wave depression in a dose-dependent manner (Fig.…”
supporting
confidence: 80%
“…Additional research is required to determine the optimal dosage and timing of administration of fasudil to obtain its maximum efficacy. ECG changes induced by vasopressin indicated a subendocardiac ischemia (17). Vasopressin is considered to be a vasoconstrictor of the coronary artery (18).…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report, 5) the fall of the Swave was regarded as the fall of ST. Maximal S-wave depression was observed about 4 min after AVP injection (data not shown), and is consistent with the results of previous reports. [7][8][9] Benidipine signiˆcant-ly inhibited the depression at 3 and 10 mg/kg in a dose-dependent manner (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…4) AVP-induced angina is a useful model for evaluating the e‹cacy of compounds in vasospastic angina. [5][6][7][8] Karasawa et al 5) reported that benidipine has beneˆ-cial eŠects in various experimental angina models, including the AVP-induced angina model. We have demonstrated recently that the antianginal e‹cacy of benidipine 10 mg/kg was similar to that of diltiazem 1000 mg/kg in the AVP-induced angina rat model, indicating that benidipine exerts potent antivasospastic anginal eŠects.…”
Section: Introductionmentioning
confidence: 99%